Features of the United Nations Development Program in Eastern European Countries - Галина Луцшин; Ірина Климчук (Історико-політичні проблеми сучасного світу)
The article is devoted to the study of the peculiarities of the functioning of the United Nations Development Program in Eastern Europe. Particular attention was focused on researching and deepening knowledge about the peculiarities of the formation and the historical basis of the United Nations Development Program. The whole historical period of the development process of UNDP is divided into stages or decades, each of which was marked by a certain event. After analyzing the structure and responsibilities of UNDP, we determined that the system of organs is quite well-formed and successfully functioning. The main body is the Executive Board, which implements and coordinates UNDP policy, makes decisions and decisions. A separate accountable body is the Bureau of the Executive Council, which advocates organizational and formal issues. In the hierarchy of organs, there is such a concept as “regional groups” – a certain number of countries that represent the region of the world. The regional group of Eastern European countries includes 4 countries: Albania, Belarus, Moldova, Ukraine. Thus, to study the functioning of the UN Development Program in Eastern Europe, Moldova, Belarus, and Ukraine were selected. Each of the countries studied, have its own programs, especially their implementation procedure, the budget and the areas they are targeting. The mobility and flexibility of UNDP make it possible to adapt the peculiar and sometimes even very specific character of the country’s activities.